The Relationship between Spiritual Quotient of Managers with Organizational Commitment of Staffs in Tehran University of Medical Sciences - Zeynab Rajabnezhad; Hossein Dargahi; Hamideh Reshadatjo (Tehran University of Medical Sciences, 2017)
Background & Aim: Spiritual quotient is an essential factor of managers' competencies for development of organizations. The managers need high spiritual quotient to impress the staffs' organizational commitment. This research is aimed to determine the correlation between the managers' spiritual quotient with the employees organizational commitment in Tehran University of Medical Sciences (TUMS). Materials and Methods: This research was a descriptive-analytical, and cross-section study that induced in TUMS headquarters among 80 of the managers and 225 of the staffs at 2014-2015. The research tools were two questionnaires, including spiritual quotient and organizational commitment that used after the validity and reliability of these questionnaires was confirmed. The data was analyzed by SPSS software, average and standard deviation, for descriptive results, and used T-Test, One-Way Variance Analysis, and Pearson technique for analytical statistics.  Results: Average of the managers' spiritual quotient was desired. Although, the average of the staffs organizational commitment was moderate. There was a significant correlation between spiritual quotient of managers with organizational commitment of the staffs (p=0.034).  Conclusion: The managers should emphasize to develop their spiritual quotient in order to promote the organizational commitment of the staffs. Using organizational psychologist to develop this relationship is our suggestion.